Integrated management of major diseases of cauliflower (Brassica oleracea var botrytis subvar cauliflora) - SHARMA, PRATIBHA; SHARMA, S R; SAIN, S K; DHANDAPANI, A (The Indian Journal of Agricultural Sciences, 2011)
Three disease management modules, viz biological, chemical and integrated disease management (lDM), were tested during 2002-04 for their efficacy against leafspot [Alternaria hrassicicola (Schw) Wiltshire], downy mildew [Perenospora parasitica (Pers.ex Fr.) Fr.] and stalk rot [Sclerotinia sclerotiorum (Lib.) de Bary] of cauliflower [Brassica oleracea L.var botrytis subvar cauliflora DC] at 2 different locations, viz New Delhi and Sikar (Rajasthan).That maximum disease control was achieved by IDM(69.7%), followed by chemical (75.5%) and biological module (86.4%). However, the maximum increase in yield (163.32%) was observed with the application ofIDM module, followed by biological (130.36%) and chemical (103.29%), whereas it was 167.85, 135.59 and 107°16 at Sikar (Rajasthan) in IDM, biological and chemical modules respectively.